THE SOURCES OF RESISTANCE GENES OF WHEAT TO LEAF AND STEM PATHOGENS ON THE TERRITORY OF THE NOVOSIBIRSK REGION - L. Р. Sochalova (Зерновое хозяйство России, 2018)
According to the study of more than 1000 genotypes of soft spring wheat from the world collection of IPI grown in the conditions of isolated infectious farm in the village of Michurinsky (the Novosibirsk region, Western Siberia) we developed 80 reliable sources of Lr, Sr and Pm-genes of resistance and combination of genes (of specific and age resistance), which can be interesting as an initial material to migrating diseases (brown rust and powdery mildew) on the territory of the Novosibirsk region. The study of resistance to brown rust was carried out with the artificial infection and the study of resistance to stem rust and powdery mildew was carried out with the natural provocative infection. We could find the sources of the new efficient genes because of the change in a set of the pathogens on the territory of the region and due to a loss of resistance to brown rust among the varieties with previous highly efficient gene Lr9 and their heavy infection with stem rust and powdery mildew. Such sources of the efficient genes as from Lr to Aegilops speltoides (с Lr28, Lr35/Sr39, Lr47), Lr48, Lr49, LrAg.i./PmAg.i, LrKu/PmKu, LrBel/PmBel, Lr24/Sr24, Lr19/Sr25+Lr26/Sr31, Lr13+Lr37/Sr38+Sr36+Sr2, Pm6+Pm3d+Pm1; Pm6+Pm4b+Pm3d+Pm2; Pm4b+Pm5+Pm1; Pm4b+Pm5 Pm4b+Pm3d have a special value for acquiring of the crop immunity to these pathogens.